2010
DOI: 10.1073/pnas.1006026107
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex structures in RNA stimulate mitochondrial transcription termination and primer formation

Abstract: The human mitochondrial transcription machinery generates the primers required for initiation of leading-strand DNA replication. According to one model, the 3′ end of the primer is defined by transcription termination at conserved sequence block II (CSB II) in the mitochondrial DNA control region. We here demonstrate that this site-specific termination event is caused by G-quadruplex structures formed in nascent RNA upon transcription of CSB II. We also demonstrate that a poly-dT stretch downstream of CSB II h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 30 publications
5
157
1
Order By: Relevance
“…Mitochondrial transcription creates primers in a CG-rich element, generally termed conserved sequence block II (CSBII), required for the initiation of leading strand DNA replication. G-quadruplexes formed by RNA result in transcription termination and dictate primer formation for DNA synthesis initiation (77). More recently, Wanrooij et al (78) reported that the mitochondrial RNA primer required for the leading strand origin of mtDNA replication forms a hybrid G-quadruplex between RNA and DNA in CSBII and that this quadruplex formation plays a critical role in determining the rate of DNA synthesis initiation in human mitochondria by influencing the architecture and persistence of an RNA-DNA hybrid (R-loop) residing at the leading strand origin of DNA replication.…”
Section: Mitochondrial Deletions Associated With Potential G-quadruplmentioning
confidence: 99%
“…Mitochondrial transcription creates primers in a CG-rich element, generally termed conserved sequence block II (CSBII), required for the initiation of leading strand DNA replication. G-quadruplexes formed by RNA result in transcription termination and dictate primer formation for DNA synthesis initiation (77). More recently, Wanrooij et al (78) reported that the mitochondrial RNA primer required for the leading strand origin of mtDNA replication forms a hybrid G-quadruplex between RNA and DNA in CSBII and that this quadruplex formation plays a critical role in determining the rate of DNA synthesis initiation in human mitochondria by influencing the architecture and persistence of an RNA-DNA hybrid (R-loop) residing at the leading strand origin of DNA replication.…”
Section: Mitochondrial Deletions Associated With Potential G-quadruplmentioning
confidence: 99%
“…The mitochondrial transcription machinery, finally, also generates the RNA primer needed for initiation of heavy strand DNA synthesis. To this end, in mammals, a G-quadruplex structure is utilised to prematurely terminate transcription from the L-strand promoter (Wanrooij et al, 2010).…”
Section: Transcriptomementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] In addition, RNA G-quadruplex structures can also stimulate mitochondrial transcription termination 12 and regulate alternative splicing in TP53 intron 3. 13 In addition, a G-quadruplex close to a cleavage sites in the 3' UTR of insulinlike growth factor II mRNA has been proposed and its structure formation has been demonstrated in vitro.…”
Section: Introductionmentioning
confidence: 99%